Identifying Clinical Factors Which Predict for Early Failure Patterns Following Resection for Pancreatic Adenocarcinoma in Patients Who Received Adjuvant Chemotherapy Without Chemoradiation - Walston, Steve (Am J Clin Oncol, 2018)
OBJECTIVES: The role of radiation therapy (RT) in resected pancreatic cancer (PC) remains incompletely defined. We sought to determine clinical variables which predict for local-regional recurrence to help select patients for adjuvant RT. METHODS: We identified 73 patients with PC who underwent resection and adjuvant gemcitabine-based chemotherapy alone. We performed detailed radiologic analysis of first patterns of failure. Local-regional recurrence was defined as recurrence of PC within standard post-operative radiation volumes. Univariate analyses (UVA) were conducted using the Kaplan-Meier method and multivariate analyses (MVA) utilized the Cox proportional hazard ratio model. Factors significant on UVA were used for MVA. RESULTS: At median follow up of 20 months, rates of local-regional recurrence only (LRRO) were 24.7%, local-regional recurrence as a component of any failure (LRR) 68.5%, metastatic recurrence as a component of any failure (MR) 65.8%, and overall disease recurrence (OR) 90.5%. On UVA, elevated post-operative CA 19-9 (>90 U/mL), pathological lymph node positive (pLN+) disease, and higher tumor grade were associated with increased LRR, MR, and OR. On MVA, elevated post-operative CA 19-9 and pLN+ were associated with increased MR and OR. Additionally, positive resection margin was associated with increased LRRO on both UVA and MVA. CONCLUSIONS: About 25% of patients with PC treated without adjuvant RT develop LRRO as initial failure. The only independent predictor of LRRO was positive margin, while elevated post-operative CA 19-9 and pLN+ were associated with predicting MR and OS. These data may help determine which patients benefit from intensification of local therapy with radiation.